The Significance of The Detection of Serum Lactate Dehydrogenase, Hypersensitive C-Reactive Protein, and N-Terminal Pro-Brain Natriuretic Peptide for the Evaluation of the Severity and Progression of Pediatric Patients with Traumatic Brain Injury - Liu, Yu; Yang, Peng; Liu, Hao-Cheng; Sun, Si; Zhang, Jia-Liang; Kang, Jun (Current neurovascular research, 2022)
This study aimed to investigate changes in the levels of serum lactate dehydrogenase (LDH), hypersensitive C-reactive protein (hs-CRP), and N-terminal pro-brain natriuretic peptide (NT-proBNP) in pediatric patients with traumatic brain injury and the clinical significance of detecting these changes for the evaluation of injury severity and patient progress. A retrospective study was conducted on 40 pediatric patients admitted to the Tongren Hospital of China Capital Medical University with traumatic brain injury between January 2018 and December 2019. Immunoturbidimetric assay and electrochemiluminescence were used to detect the serum levels of LDH, hs-CRP, and NT-proBNP. Correlation analysis was used to determine the degree of association between the indicators and the sensitivity and specificity of each indicator. The serum levels of LDH, hs-CRP, and NT-proBNP in the poor-prognosis group were higher than those in the good-prognosis group, and the differences were statistically significant (P < 0.05). The detection of serum LDH, hs-CRP, and NT-proBNP might be of great significance for the evaluation of the severity of a traumatic brain injury, disease progression, and the prognosis of pediatric patients with traumatic brain injury. The combined detection of the relevant indicators could provide more effective sensitivity and specificity and therefore offer better guidance and assistance in clinical practice.